Autoantibodies Toward ATP4A and ATP4B Subunits of Gastric Proton Pump H+, K+-ATPase Are Reliable Serological Pre-endoscopic Markers of Corpus Atrophic Gastritis. Issue 10 (6th October 2020) - Lahner, Edith; Marzinotto, Ilaria; Lampasona, Vito; Dottori, Ludovica; Bazzigaluppi, Elena; Brigatti, Cristina; Secchi, Massimiliano; Piemonti, Lorenzo; Conti, Laura; Pilozzi, Emanuela; Davidson, Howard W.; Wenzlau, Janet M.; et al.
Abstract : INTRODUCTION: Noninvasive assessment of corpus atrophic gastritis (CAG), a condition at increased risk of gastric cancer, is based on the measurement of pepsinogens, gastrin, and Helicobacter pylori antibodies. Parietal cell autoantibodies (PCAs) against the gastric proton pump (ATP4) are potential serological biomarkers of CAG. The purpose of this study was to compare the diagnostic performance of PCA and pepsinogen I tests in patients with clinical suspicion of CAG with the histopathological evaluation of gastric biopsies as reference standard. METHODS: A prospective case-finding study was performed on 218 naive adult patients (131 women, median age 65 years) who underwent gastric biopsies to confirm/exclude CAG. Patients with histopathological CAG were defined as cases, conversely as controls. Autoantibodies against the individual alpha (ATP4A) and beta (ATP4B) subunits of ATP4 were measured by luciferase immunoprecipitation, and global PCA and pepsinogen I by enzyme-linked immunosorbent assay. RESULTS: Histopathology classified 107 subjects (49%) as cases (CAG+, autoimmune 81.2%, and multifocal extensive 18.8%) and 111 subjects (51%) as controls (CAG−). In cases, ATP4A, ATP4B, and PCA titers were increased compared with controls, whereas pepsinogen I was reduced ( P < 0.0001 for all). ATP4B, ATP4A, and pepsinogen I tests showed sensitivities of 77%, 75%, and 73% and specificities of 88%, 88%, and 80%, respectively. The receiver operating characteristic (ROC) area under the ROC curve (AUC) of these serological biomarkers confirmed their ability to discriminate cases from controls (ATP4B = 0.838, ATP4A = 0.826, pepsinogen I = 0.775, and PCA = 0.805), whereas the partial ROC-pAUC90 analysis showed that the ATP4B test had the best diagnostic performance ( P = 0.008 vs ATP4; P = 0.0002 vs pepsinogen I). The presence of autoimmune or extensive gastritis was not significantly different between ATP4B positive or negative cases ( P = 0.217). DISCUSSION: PCAs are promising serological biomarkers for the identification of CAG in high-risk individuals, particularly in an autoimmune pattern but also in an extensive-multifocal atrophy pattern.